Comparison of asynchronous online versus in-person library instruction methods for teaching literature searching to graduate students. - McKeown, Sandra; Roy, Angélique; Hopman, Wilma M. (Journal of the Canadian Health Libraries Association (JCHLA), 2024)
Introduction: The objectives of this comparative study were 1) to compare the effectiveness of in-person classroom instruction versus an online video for teaching literature searching skills to graduate students, and 2) to evaluate their perceptions of the instruction methods received and their instruction preferences for learning literature searching skills. Methods: Students enrolled in a translational medicine graduate course in Fall 2022 were invited to participate in the study. Participants were randomly assigned to a control group (receiving in-person instruction) or to an intervention group (receiving a link to a narrated PowerPoint video). Using Qualtrics online survey tool, participants completed one pre-test and two posttests to assess learning and retention, and a survey to evaluate their perceptions and attitudes. Results: 12 out of 17 students participated. Both instruction methods were effective for delivering this information literacy content. The in-person group improved more than the online video group from pre- to post-test 1 and from pre- to post-test 2, but the difference was not statistically significant. However, the online video group rated the pace, perceived effectiveness, and clarity of library instruction, and their confidence to perform specific search tasks, more favourably than the in-person group, although the difference was not significant. Participants valued being able to access library training on their own schedule most of all. Discussion: The sample size for this study was small, making it difficult for differences to attain statistical significance. Creating an online video to deliver this content ended up being very time-intensive compared to providing synchronous instruction.